2023
DOI: 10.1007/s11356-023-27285-7
|View full text |Cite
|
Sign up to set email alerts
|

Bi-functional photocatalytic heterostructures combining titania thin films with carbon quantum dots (C-QDs/TiO2) for effective elimination of water pollutants

Abstract: In this study, carbon quantum dots (C-QDs), prepared via hydrothermal-microwave procedures, were successfully combined with nanostructured titania (TiO2). The photocatalytic oxidation/reduction activity of the C-QDs/TiO2 composite films was evaluated in the decomposition of organic-inorganic contaminants from aqueous solutions under UV illumination. Physicochemical characterizations were applied to investigate the crystal structure of the carbon quantum dots and the composites. It was found that the prepared C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…For example, R % was 48, 45, and 37% for carbon dots modified mesoporous organosilica as an adsorbent for the removal of Hg(II), Cu(II), and Pb(II), respectively 22 . In addition, the maximum R % of Cr(VI) by TiO 2 /CQDs was 43.39% 23 .…”
Section: Resultsmentioning
confidence: 93%
“…For example, R % was 48, 45, and 37% for carbon dots modified mesoporous organosilica as an adsorbent for the removal of Hg(II), Cu(II), and Pb(II), respectively 22 . In addition, the maximum R % of Cr(VI) by TiO 2 /CQDs was 43.39% 23 .…”
Section: Resultsmentioning
confidence: 93%
“…Through the use of trapping experiments, the mechanism of the photocatalytic reaction was examined. It was shown that the holes (h + ) are the primary active species in the photocatalytic oxidation processes and that the electron (e – ) radical species were strongly supported in the reduction of Cr 6+ and PNP …”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the holes (h + ) are the primary active species in the photocatalytic oxidation processes and that the electron (e − ) radical species were strongly supported in the reduction of Cr 6+ and PNP. 246…”
Section: White Light Emitting Diode (Wleds)mentioning
confidence: 99%
“…Next, the acquired Nyquist plots from impedance spectroscopy (Figure 7) provide insights into the charge transfer resistance of the photoexcited electron-hole pairs. The shorter semicircle diameters of the composite materials demonstrate that the incorporation of α-Fe2O3 with MoS2 improves the charge carriers' separation and limits the recombination effects [29]. Even if there is no specific tendency between the oxide quantity in the composites and reduced resistance, an obvious improvement is observed; therefore, the enhanced generation of reactive radicals is also predicted during photocatalysis compared to the reference molybdenum disulfide sample.…”
Section: Optoelectronic Propertiesmentioning
confidence: 88%
“…Following this, a doctor blade technique was utilized to fabricate a uniform 1 cm 2 active area on a clean FTO electrode. The sample was then annealed at 450 • C. The solution used for the electrochemical measurements contained a sodium sulfate (Na 2 SO 4 ) electrolyte with a concentration of 0.2 M [29].…”
Section: Materials Characterizationmentioning
confidence: 99%